Analysis of pesticide residues in vegetables purchased from local markets of Mymensingh district of Bangladesh based on QuEChERS Extraction and Gas Chromatography - Alam, Md Mahadi; Hasan, Rakibul; Rahman, S M Mizanur; Choudhury, Md Abdur Razzak; Prodhan, Mohammad Dalower Hossain (Asian-Australasian Journal of Food Safety and Security, 2022)
The study was conducted to analyze organophosphorus pesticide residues in two common vegetables (cauliflower and eggplant) collected from five local markets of Mymensingh district of Bangladesh. The collected samples were carried to the Pesticide Analytical Laboratory, Entomology Division of Bangladesh Agricultural Research Institute (BARI), Gazipur on the same sampling day. The collected samples were analyzed using Quick, Easy, Cheap, Effective, Rugged and Safe (QuEChERS) extraction technique and Gas Chromatography (GC) coupled with Flame Thermionic Detector (FTD). In total, 60 vegetable samples were analyzed in this study. Out of 30 analyzed samples of cauliflower, 5 samples (17% of the total number of samples) contained residues of dimethoate, chlorpyrifos and quinalphos, where 3 samples contained residues above the maximum residue limits (MRLs). Among the 30 analyzed samples of eggplant, 5 samples (17% of the total number of samples) contained residues of chlorpyrifos, quinalphos, and dimethoate, where only one sample contained residues above MRL. This study reflects the actual scenario of pesticide residues remain in cauliflower and eggplant collected from local markets of Mymensingh district, which will help the consumer to be aware of their health and safety. Thus, continuous monitoring of pesticide residues in vegetables should be strengthened. Asian Australas. J. Food Saf. Secur. 2022, 6 (1), 10-17